Complexidade, desenvolvimento sustentável, comunicação - o Programa um Milhão de Cisternas em comunidades do Ceará - Dias, Ana Valéria Feitosa (2004)
This study investigates the “A Million Cisterns Program” (P1MC), considering aspects of comunication and sustainability at the community of Livramento, municipality of Irauçuba, and the communitity of Araponga, municipality of Itapipoca. A field survey was carried out at both communities, consisting of oriented interviews with 31 famílies from Livramento and Araponga, and half-structured interviews with local leaders and members from the following non-governmental organizations: Esplar, Instituto Sertão, Catavento Comunicação e Educação Ambiental, Cáritas Regional, and Cáritas Diocesana de Itapipoca.Communities and entities were selected according to the schedule defined for the research, covering the pilot and transition phases of P1MC. The criteria of the number of cisterns built by the community, and of radio station. The theoretical framework was composed around three concepts: complexity, sustainable development and comunication so, the scientific cathegories of era of relationships, environmental rationality, environmental knowledge and cultural mediations were explored. The conclusion is that the P1MC, in its pilot and transition phases, is only the beginning of a process that will requires more time to its maturation. There are limitations and challenges to be won. The sustainability of the perspective of living together with and within the Brazilian semiarid tropiocs, stated by P1MC, depends directly on the pledge of the families. This, what is needed are not only objective actions of cisterns building but, mainly, the absorption of subjetive aspects of the program.